Implementation of Serverless Internet of Things Architecture in Cold Chain Monitoring - Mulyani, Aisyah; Oktiawati, Unan Yusmaniar (Department of Electrical Engineering and Informatics, Vocational College, Universitas Gadjah Mada, 2022)
With the current technological developments, the need for monitoring in cold chain logistics as well as the problem of limitations on IoT devices such as data storage and computing capabilities can be handled with the help of cloud technology. Cloud has a concept called serverless. In this study, researchers tried to examine serverless services that can be integrated with IoT devices. The IoT devices used consist of nodes and gateways. In this final project research, testing and analysis of gateway devices and serverless architecture are carried out. NodeMCU which is part of the gateway device and AWS IoT as a serverless service will be integrated in this research. The serverless architecture system that was built also has a function to store data and send notifications to the user. Meanwhile, data monitoring will be carried out through Grafana. The results of AWS IoT performance testing when integrated with IoT gateway devices through QoS testing according to the TIPHON standard are categorized as satisfactory and the implemented system functions as expected.